2021
DOI: 10.3390/nu13093262
|View full text |Cite
|
Sign up to set email alerts
|

Is Energy Expenditure or Physical Activity Considered When Energy Intake Is Measured? A Scoping Review 1975–2015

Abstract: The health-transitions humans have delivered during the 20th Century associated with the nutrition is that from undernutrition to obesity, which perseveres in the current years of the 21st Century. Energy intake (EI) is a contributing factor and therefore a fascination in nutritional sciences. However, energy expenditure (EE) has not been usually considered as a conjoint factor. Thus, this study aimed to review if studies on adults consider data on dietary intake, specifically EI, and included data on EE and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…However, a limitation is that this paper focuses only on nutrition best practices in response to the focus of this special issue on the nutritional contributions to health outcomes in early childhood. We encourage future research to consider multiple contributors to health outcomes beyond nutrition such as physical activity [ 82 ].…”
Section: Limitationsmentioning
confidence: 99%
“…However, a limitation is that this paper focuses only on nutrition best practices in response to the focus of this special issue on the nutritional contributions to health outcomes in early childhood. We encourage future research to consider multiple contributors to health outcomes beyond nutrition such as physical activity [ 82 ].…”
Section: Limitationsmentioning
confidence: 99%
“…As a result, obesity has imposed a substantial economic burden on the Libyan state as a whole, which was estimated to be 65% of the Libyan state health budget [4,5,11]. When considering factors that may contribute to or protect against obesity, it is important to consider both sides of the energy-balance equation: on the one hand, the factors related to energy intake (involving food consumption and beverage intake) and, on the other hand, the factors related to energy expenditure (involving physical activity and sedentary lifestyle) [12,13]. It has been suggested that the more risk factors an individual has, the greater the chance of that person developing obesity and dying from it [14].…”
Section: Introductionmentioning
confidence: 99%